2006
DOI: 10.1111/j.1469-1795.2006.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete reporting of whale, dolphin and porpoise ‘bycatch’ revealed by molecular monitoring of Korean markets

Abstract: We report the results of molecular monitoring of 'whalemeat' markets in the Republic of (South) Korea based on nine systematic surveys from February 2003 to February 2005. As Korea has no programme of commercial or scientific whaling and there is a closure on the hunting of dolphins and porpoises, the only legal source of these products was assumed to be incidental fisheries mortalities ('bycatch') as reported by the government to the International Whaling Commission. Species identification of 357 products usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 19 publications
0
41
1
1
Order By: Relevance
“…In New Zealand, Bryde's whales are reported only for the north-eastern coast of the North Island (Baker & Madon 2007, Wiseman 2008) and occur year-round in the Hauraki Gulf (Behrens & Constantine 2008, Wiseman et al 2011). The whales have been ob served throughout the inner Gulf in water depths ranging from 12 to 60 m (Wiseman et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, Bryde's whales are reported only for the north-eastern coast of the North Island (Baker & Madon 2007, Wiseman 2008) and occur year-round in the Hauraki Gulf (Behrens & Constantine 2008, Wiseman et al 2011). The whales have been ob served throughout the inner Gulf in water depths ranging from 12 to 60 m (Wiseman et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these have already been utilized to reveal discrepancies in reported marine mammal bycatch, to determine the magnitude of trade and to develop kits that rapidly identify marine mammal species in situ in Asian markets (Baker et al, 2006(Baker et al, , 2007Lukoschek et al, 2009;Lo et al, 2013). These tools, designed specifically for non-specialists, will allow quantitative data collection both on type and volume of marine mammal parts in Asian markets.…”
Section: Lessons and Conclusion From Terrestrial Wildlife Trade Studiesmentioning
confidence: 99%
“…Actually, several studies reported that there was a high number of illegal, unreported or unregulated catches for this stock (Baker et al 2006(Baker et al , 2007Lukoschek et al 2009). Also, the default value of R max was used to estimate PBR for minke whales in this area because the data on R max were insufficient.…”
Section: Discussionmentioning
confidence: 99%